2002
DOI: 10.1007/s11910-002-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Semantic memory

Abstract: Our concepts about objects, states, and events are stored in a cognitive structure termed semantic memory. There are several types of neurologic disorders that may cause impairments of semantic memory. Clinical evaluations of these impairments are complex, because semantic memory is linked to other cognitive systems that, when damaged, may produce related syndromes or difficulties. In an attempt to gain further understanding of these breakdown patterns, we review data from both neuropsychologic and brain activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Although the right hemisphere (especially the right parietal cortex) is traditionally coupled with visuospatial function and CDT performance has been explained at least partly by this function [3][4][5] , no previous functional imaging study has provided any evidence for the relationship between CDT performance and the right hemisphere function in AD. In a SPECT study adopting the voxel-based analysis, Nagahama et al [6] reported that the impaired CDT performance in patients with AD is related to the dysfunction in the left posterior temporal cortex, which may be related to semantic memory [24] . On the basis of their results, they suggested that the impaired CDT performance in patients with AD might be associated mainly with their deficit in semantic knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Although the right hemisphere (especially the right parietal cortex) is traditionally coupled with visuospatial function and CDT performance has been explained at least partly by this function [3][4][5] , no previous functional imaging study has provided any evidence for the relationship between CDT performance and the right hemisphere function in AD. In a SPECT study adopting the voxel-based analysis, Nagahama et al [6] reported that the impaired CDT performance in patients with AD is related to the dysfunction in the left posterior temporal cortex, which may be related to semantic memory [24] . On the basis of their results, they suggested that the impaired CDT performance in patients with AD might be associated mainly with their deficit in semantic knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The left posterolateral temporal association cortex is implicated in semantic memory processing. Functional neuroimaging studies of lexical semantic memory frequently show posterolateral temporal activation for multiple semantic categories, and point towards the posterior region of the left temporal lobe as the major neuroanatomic substrate of semantic memory [19] . A previous study suggested that the CDT defi cits in AD are related to semantic impairments [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Semantic memory refers to the memory which is learned by people, such as meanings, understandings, conceptbased knowledge, and work-related skills, and facts [50]. Episodic memory refers to the memory which is explicitly located in the past involving the specific events and situations, such as times, places, associated emotions, and other contextual knowledge [51], [52].…”
Section: B Encoding Episodic and Semantic Features (Block 1)mentioning
confidence: 99%